Online Consumer Behavior in Buying Samsung Smartphones - Agus Suryo Murtopo; Muhammad Husin Nur Muzakki (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
Purchasing decision is the culmination of consumer behavior, in which finally, the consumers will do purchase having passed through some stages of consumer behavior. In this research, consumer behaviors being the variable of research are price, brandtrust, and online service, while the variable affected is purchasing decision. Purchasing decision implemented online is, of course, more complex than the one implemented directly, in which buyers interact face to face with the sellers. The objective of research is to analyze the effect of price, brandtrust, and online service on purchasing decision made in online purchase in the students of Faculty of Economics and Business, Sebelas Maret University (Universitas Sebelas Maret). Questionnaire was used as an instrument of collecting data in this research and SPSS version 24 software was used to analyze data. Data analysis was carried out using a multiple linear regression. The result of research shows that price, brandtrust and online service quality affect the decision of purchasing Samsung smartphone positively and significantly, either partially or simultaneously.